Effect of ursolic acid in attenuating chronic constriction injury‐induced neuropathic pain in rats. (5th August 2016) - Bhat, Rafia A.; Lingaraju, Madhu C.; Pathak, Nitya N.; Kalra, Jaspreet; Kumar, Dhirendra; Kumar, Dinesh; Tandan, Surendra K.
Abstract: Ursolic acid (UA; 3b‐hydroxy‐12‐urs‐12‐en‐28‐oic acid), a natural pentacyclic triterpenoid carboxylic acid, has been known to possess potent anti‐inflammatory, antioxidant, and antinociceptive effects in various animal models. Therefore, this study was designed to investigate the antihyperalgesic, anti‐inflammatory, and antioxidant effects of UA at 5, 10, and 20 mg/kg of doses via per os ( p.o.) route for 14 days in chronic constriction injury (CCI)‐induced neuropathic pain in rats. Pain behavior in rats was evaluated before and after UA administration via mechanical and heat hyperalgesia. CCI caused significant increase in levels of pro‐inflammatory cytokines and oxido‐nitrosative stress. In addition, significant increase in myeloperoxidase, malondialdehyde, protein carbonyl, nitric oxide (NO), and total oxidant status (TOS) levels in sciatic nerve and spinal cord concomitant with mechanical and heat hyperalgesia is also noted for CCI‐induced neuropathic pain. Administration of UA significantly reduced the increased levels of pro‐inflammatory cytokines and TOS. Further, reduced glutathione is also restored by UA. UA also showed in vitro NO and superoxide radical scavenging activity. UA has a potential in attenuating neuropathic pain behavior in CCI model which may possibly be attributed to its anti‐inflammatory and antioxidant properties.